A review of Vertical and Spatial Variations of Canopy Insects in Secondary Forests in Central Japan and East Java, Indonesia - Leksono, Amin Setyo; Nakagoshi, Nobukazu (Proceeding International Conference on Global Resource Conservation, 2015)
The vertical and spatial variations in the abundance of canopy insects werecompared between secondary forests in Kanazawa, Japan and Trawas, East Java, Indonesia. The patterns of canopy insect abundance and composition change with layer and site weredetermined. The study in Central Japan was conducted at a mosaic habitat of a suburban forest in Kanazawa, Central Japan. Two patches were selected for sampling: a young deciduous patch and a mixed vegetation patch. Canopy insects were collected 12 times from June to October 2003. Another study site is located in Trawas, East Java, Indonesia. Insect sampling was performed at three sites along a gradient of anthropogenic disturbances, from a less-disturbed site in an upper hilly area, through a partly-disturbed site, to a highly-disturbed site. Samplings were performed by using window traps, suspended in the canopy layer and in the understory layer. This study revealed that canopy insect communities vary among canopy layers and sites. However, this study did not indicate consistent insect stratification between regions. Data in temperate region showed that the abundance of canopy insects is greater in the canopy layer than in the understory layer. In tropical region, the abundance of canopy insects between understory and canopy layer was similar. The young deciduous patch consisted of more individuals of canopy insects than in the mixed vegetation patch. Our study in tropical region demonstrated significant effects of disturbance on the abundance and family richness of canopy insects. The overall insect abundances and richness differed among sites.Keywords: Anthropogenic disturbance; canopy insect community; secondary forest; temperate and tropical region; window trap